Professional burnout among medical students: Systematic literature review and meta-analysis. (1st February 2019) - Erschens, Rebecca; Keifenheim, Katharina Eva; Herrmann-Werner, Anne; Loda, Teresa; Schwille-Kiuntke, Juliane; Bugaj, Till Johannes; Nikendei, Christoph; Huhn, Daniel; Zipfel, Stephan; Junne, Florian
Abstract: Background: This systematic review and meta-analysis aim to summarize the available evidence on the prevalence of professional burnout among medical students. Methods: The review was performed according to the PRISMA guidelines. Databases were systematically searched for peer-reviewed articles, reporting burnout among medical students published between 2000 and 2017. The meta-analysis was conducted on the available data on burnout rates in medical students measured with the Maslach Burnout Inventory (MBI-HSS). Results: Fifty-eight out of 3006 studies were found eligible for inclusion. Twelve of these studies met the criteria for meta-analysis. Weighted mean values for the three sub-dimensions of the MBI–HSS were M = 22.93 (SD = 10.25) for Emotional Exhaustion, M = 8.88 (SD = 5.64) for Depersonalization, and M = 35.11 (SD = 8.03) for Personal Accomplishment. Prevalence rates for professional burnout ranged from 7.0% to 75.2%, depending on country-specific factors, applied instruments, cutoff-criteria for burnout symptomatology. Conclusion: This review underlines the burden of burnout among medical students. Future research should explicitly focus on specific context factors and student group under investigation. Such efforts are necessary to control for context-dependent confounders in research on medical students' mental health impairment to enable more meaningful comparisons and adequate prevention strategies.